Getting started with the Internet of things - Pfister, Cuno. (Mumbai. : Shroff Publisher & Dis Pvt.Ltd, 2018)
"What is the Internet of Things? It's countless embedded computers, sensors, and actuators all connected online. If you have basic programming skills, you can use these powerful little devices to create a variety of useful systems--such as devices that react to real-world events and take action. This hands-on guide shows you how to start building your own ... projects. Learn to program embedded devices using the .NET Micro Framework and the Netduino Plus board. Then connect your devices to the Internet with Pachube, a cloud platform for sharing real-time sensor data. ... Develop programs with simple outputs (actuators) and inputs (sensors); learn about the Internet of Things and the Web of Things; build client programs that push sensor readings from a device to a web service; create server programs that allow you to control a device over the Web; get example programs that you can compile with Visual Studio on Windows or Mono on Mac OS X and Linux"--P. [4] of cover.
Includes index.
Keywords: Microcontrollers -- Programming; Detectors -- Design and construction